2005
DOI: 10.1242/jcs.02664
|View full text |Cite
|
Sign up to set email alerts
|

Cell wall remodeling at the fission yeast cell division site requires the Rho-GEF Rgf3p

Abstract: IntroductionCytokinesis is the final step of the cell cycle that results in the formation of two daughter cells from one. This process is regulated temporally and spatially such that the replicated and segregated chromosomes are evenly divided between daughter cells. The genetically tractable yeast Schizosaccharomyces pombe is an excellent organism for studying cytokinesis as it divides by medial fission following assembly and contraction of an actomyosin-based cleavage apparatus that directs placement and ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
99
0
18

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(122 citation statements)
references
References 59 publications
(90 reference statements)
5
99
0
18
Order By: Relevance
“…Interestingly, depletion of Rho1p or mutation of one of its exchange factors, Rgf3, caused a cell lysis phenotype (Arellano et al 1997;Tajadura et al 2004;Morrell-Falvey et al 2005;Mutoh et al 2005) that is extremely similar to that which we observed in the sid2-250 mutant cells at low restrictive temperatures. We decided to examine whether enhancing 1,3-bd-glucan synthesis by slightly overexpressing Rho1p can rescue the lysis phenotype in sid2-250 mutant cells.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…Interestingly, depletion of Rho1p or mutation of one of its exchange factors, Rgf3, caused a cell lysis phenotype (Arellano et al 1997;Tajadura et al 2004;Morrell-Falvey et al 2005;Mutoh et al 2005) that is extremely similar to that which we observed in the sid2-250 mutant cells at low restrictive temperatures. We decided to examine whether enhancing 1,3-bd-glucan synthesis by slightly overexpressing Rho1p can rescue the lysis phenotype in sid2-250 mutant cells.…”
Section: Resultssupporting
confidence: 75%
“…In addition, the lysis of cells caused by switching off Rgf3p can be rescued by sorbitol, while Rho1p-depleted cells cannot, suggesting that Rgf3p controls a subset of the functions of Rho1p in cell wall biosynthesis (Arellano et al 1997;Tajadura et al 2004;Morrell-Falvey et al 2005;Mutoh et al 2005). More interestingly, both Rho1p and Rgf3p localize at the septum (Arellano et al 1997;Tajadura et al 2004;Morrell-Falvey et al 2005;Mutoh et al 2005), strongly suggesting that they are involved in cell wall biosynthesis at the septum. Thus, it is an intriguing possibility that the SIN targets Rho1 as one of its downstream effectors; this could be achieved by activating Rgf3, which is a specific Rho1 GEF for its function in cell wall biosynthesis (Tajadura et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of rgf1 + , encoding the main Rho1-GEF (García et al 2006), rescued the growth of rho1-596 mutant cells, but overexpression of rgf3 + , encoding the cytokinesis specific Rho1-GEF (Tajadura et al 2004;Morrell-Falvey et al 2005;Mutoh et al 2005), did not ( Figure S1A). These results suggest that rho1-596 growth defects are not restricted to cytokinesis.…”
Section: Rho1-596 Is a Thermosensitive Strain With Severe Cell Wall Dmentioning
confidence: 99%
“…The regulation of Rho1p in fission yeast involves at least three GEFs (Rgf1p, Rgf2p, and Rgf3p) and several putative GAPs (Rga1p,Rga5p,and Rga8p). rgf3 ϩ is an essential gene and the protein specifically activates Rho1p during cytokinesis (Tajadura et al, 2004;Morrell-Falvey et al, 2005;Mutoh et al, 2005). Rgf1p and Rgf2p are the closest relatives, and they provide a redundant function for the activation of Rho1p (Mutoh et al, 2005).…”
Section: Introductionmentioning
confidence: 99%